The evidence for increased L1 activity in the site of human adult brain neurogenesis - Kurnosov, Alexey A .; Khodosevich, Konstantin (PLOS ONE, 2015)
Retroelement activity is a common source of polymorphisms in human genome. The mechanism whereby retroelements contribute to the intraindividual genetic heterogeneity by inserting into the DNA of somatic cells is gaining increasing attention. Brain tissues are suspected to accumulate genetic heterogeneity as a result of the retroelements somatic activity. This study aims to expand our understanding of the role retroelements play in generating somatic mosaicism of neural tissues. Whole-genome Alu and L1 profiling of genomic DNA extracted from the cerebellum, frontal cortex, subventricular zone, dentate gyrus, and the myocardium revealed hundreds of somatic insertions in each of the analyzed tissues. Interestingly, the highest concentration of such insertions was detected in the dentate gyrus—the hotspot of adult neurogenesis. Insertions of retroelements and their activity could produce genetically diverse neuronal subsets, which can be involved in hippocampal-dependent learning and memory.